OCTOPUS 8 narradores argentinos contemporáneos - Barbieri, Osvaldo J.; Bernatek, Carlos; Butti, Enrique M.; Catania, Carlos; Gómez, Carlos María; Morán, Carlos Roberto; Pagés, José Luis; VÍttori, José Luis (Universidad Nacional del Litoral, 1998)
Contenido : BARBIERI, Osvaldo J.; BERNATEK, Carlos; BUTTI, Enrique; CATANIA, Carlos; GOMEZ, Carlos Ma.; MORAN, Carlos Roberto; PAGES, José Luis; VITTORI, José Luis